What Sparkles Does Not Always Shine: A Study of Segregation and Gentrification in The Neighborhood of Runnymede-Bloor West Village as it Relates to the Wider City of Toronto - Topp, Simon (Contemporary Kanata: Interdisciplinary Approaches To Canadian Studies, 2021)
This paper is an ethnographic and sociological study of the neighborhood of Runnymede-Bloor West Village, identifying trends and drawing conclusions based on statistical data, academic theory, and notes taken during research trips. It is also worth noting that this study was conducted in January of 2020 before the Global pandemic was declared. Focusing on gentrification, segregation, and inequality, I identify that this neighborhood is part of a growing trend in Toronto of the increasing severity of all three of these issues. Runnymede-Bloor West Village is quickly becoming one of Toronto’s wealthiest neighborhoods, with the average household income increasing substantially. While this will certainly make real estate agents happy and will probably provide the city with more property tax, it also has the effect of pushing less affluent people out, as increasing living costs make their continued residence in Runnymede-Bloor West Village unaffordable. It also influences the local businesses, as businesses that do not cater to the new influx of affluent residents go out of business, either because their customer base has left or because they can no longer afford to pay their rent. I also identify the increased segregation of the neighborhood, as the racialized character of income inequality in Toronto results in people of color being priced out. Finally, I recommend that the solution to much of this increased inequality is the building of more affordable housing and restrictions of the building of unaffordable housing. Much of this will require the actions of a progressive, engaged local government. Hopefully, these steps will be able to halt or even reverse the trend of an ever-increasing cost of living, provide the local businesses with customers who do not have to spend most of their income on housing costs, and provide a short term solution to the issue of income and ethnicity-based segregation in Toronto.